THE ROLE OF PLAY THERAPY IN INCREASING READING MOTIVATION IN CHILDREN WITH SPECIAL EDUCATIONAL NEEDS (British Journal of Global Ecology and Sustainable Development, 2022)
The article discusses the use and importance of play therapy to increase learning motivation in the process of teaching children with special educational needs.